KORELASI ANTARA PRESTASI SISWA DALAM MATA PELAJARAN AKIDAH AKHLAK DENGAN KEPATUHAN TERHADAP PERATURAN DI SEKOLAH MADRASAH ALIYAH SWASTA YAYASAN PENDIDIKAN HAJI DATUK ABDULLAH TANJUNG MORAWA - sarah, sarah (Fakultas Agama Islam, 2023)
The research objectives are; First, to determine student achievement in the subject of moral beliefs. Second, to determine student compliance with regulations. Third, to determine the correlation between student achievement in the subject of moral beliefs and compliance with regulations at the Haji Datuk Abdullah Tanjung Morawa Private Madrasah Aliyah school. This type of research is quantitative, data collection techniques are carried out using observation, documentation and questionnaire methods. The data that has been obtained is then analyzed using statistical analysis using the product moment correlation formula. The results of the research show that student achievement in the subject of moral beliefs with the highest score is 95 and the lowest is 75. Calculation of the average student achievement in the subject of moral beliefs shows that the score is 81, including in the medium category which is located in the interval 81-85. From the results of calculating the average compliance with school regulations, it is known that the value is 74.16, namely in the interval 71-76 and is included in the medium category. According to calculations using the product moment correlation formula, namely the calculated r value = 0.509 and the r table value at a significant level of 5% from the r table distribution table, and the formula for the r table (df=n-2) df=36-2=34 then, rtable of 34 is 0.339. Because r countr table, the results are significant. This means that the hypothesis which states that